2002
DOI: 10.4314/sinet.v25i2.18080
|View full text |Cite
|
Sign up to set email alerts
|

Variation and association analysis in grass pea (<i>Lathyrus sativus</i> L.)

Abstract: ABSTRACT:The study was conducted on 50 landrace populations of grass pea at Adet Research Center, Ethiopia, using Randomised Complete Block Design in three replications to determine morphological variability and character associations. Evaluations were made on plant and yield characters from eight plants tagged randomly from each plot. The data were subjected to Analysis of Variance (ANOVA), heritability, correlation and cluster analyses. Higher mean and CV values were recorded for most of the agronomic traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 8 publications
6
13
1
Order By: Relevance
“…These results indicated that high yielding and late flowering genotypes were also low ODAP content. Likewise a negative correlation was reported between ODAP and seed yield by Tadesse and Bekele (2003) and . However positive association between ODAP and seed yield was reported by Hanbury et al (1999).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…These results indicated that high yielding and late flowering genotypes were also low ODAP content. Likewise a negative correlation was reported between ODAP and seed yield by Tadesse and Bekele (2003) and . However positive association between ODAP and seed yield was reported by Hanbury et al (1999).…”
Section: Resultsmentioning
confidence: 60%
“…However, ODAP content in the present genotypes is relatively high compared to 2 mg/g content reported as critical value by Abd El- Moneim et al (2010). Low ODAP content is one of the main targets of the grass pea breeding besides high grain yield and protein content (Tadesse and Bekele, 2003). ODAP is mainly controlled by genetic factors and lesser by environment (Hanbury et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Also, mean of data used for analysis and simple linear correlation coefficients were computed then factor analysis on the base of major factors analysis and varimax rotations was done on the data. The factors which had a root bigger than one were selected and were used to form factorial coefficients matrix (Sharma, 1985;Tadesse and Bekele, 2001). Also eigen values, percent variance, variance, and cumulative percentage share of each of the extracted factors were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…By means of varimax rotation which maximizes the variance among the factors, the factors which justify more percentage of variations among the characters have had more importance and must be studied. So, the effective characters on each factor are identified and the factors are named according to the most effective characters (Tadesse and Bekele, 2001). In factor analysis by means of major factors analysis and on base of specific numbers larger than 1, under normal and stress conditions three factors were identified under normal irrigation and four factors were identified under drought stress and they all together justify 91.23 and 92.43 percent of existent variation among the characters, respectively (Table 6 and 7).…”
Section: Factor Analysismentioning
confidence: 99%
“…Its seed usually reach a harvestable stage within five to six months from planting depending on the environment and the plant dies after the seeds have matured [14]. In addition to its consumption, the growing women sell this crop and generate their own money.…”
Section: Introductionmentioning
confidence: 99%